2022
DOI: 10.7759/cureus.30535
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease: Its Relationship With Obesity

Abstract: A significant obstacle to avoiding chronic illnesses in people worldwide is the increasing development of obesity. They are supported by economic expansion, mechanized transportation, a rise in sedentary behavior, and a switch from a wholesome, healthy diet to processed foods and high-calorie meals, including fast food and sugary drinks. Many developed or emerging countries have seen the prevalence of obesity in their populations increase twice over. Therefore, it must now be treated as a disease of concern. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…As possible explanation we find the lack of information on proteinuria. The obesity has been recognized as a risk factor of CKD [9].…”
Section: Discussionmentioning
confidence: 99%
“…As possible explanation we find the lack of information on proteinuria. The obesity has been recognized as a risk factor of CKD [9].…”
Section: Discussionmentioning
confidence: 99%
“…These results need to be confirmed with the inclusion of larger study groups. Discussing the importance of obesity in the development of CKD, Prasad et al [1] and Yim et al [2] point out that children born to obese mothers are at greater risk of developing the disease, which would also need to be included in future studies, rather including adults. Indeed, organ changes associated with obesity increase gradually, and obesity and hyperlipidaemia themselves affect kidneys not only directly, but also by inducing cardiovascular disease [24].…”
Section: Discussionmentioning
confidence: 99%
“…It also causes haemodynamic and histological changes in kidneys and is considered an important cause of chronic kidney disease (CKD) in adults. Importantly, obesity from early childhood can result in early onset of CKD [1,2]. Vivante et al found that the risk of end-stage renal disease (ESRD) in obese 17-year-olds is 2.4 times higher over a follow-up of 25 years than in non-obese subjects [3].…”
Section: Introductionmentioning
confidence: 99%
“…While obesity predominated in women (41% vs. 32.3%), being overweight was more frequent in men (41.2% vs. 35.8%) [ 7 ]. Obesity/overweight (O/O), mainly in adults, increases the risk of developing diabetes, high blood pressure, dyslipidemia, ischemic heart disease, stroke, chronic kidney disease, and many other dangerous comorbid conditions [ 8 , 9 , 10 ]. O/O women with the so-called metabolic syndrome (MS) are known to be at high risk for CVD, still more significantly than their male counterparts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%